2013
DOI: 10.1093/ejcts/ezs622
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results in patients with pathological complete response after induction radiochemotherapy followed by surgery for locally advanced non-small-cell lung cancer

Abstract: After induction radiochemotherapy followed by surgery in locally advanced NSCLC, a pCR is achieved in a remarkable proportion of cases (27% in our experience). In such patients, a rewarding LTS (64% at 5 years) could be expected, especially when a single N2 station is involved at diagnosis or when an adjuvant treatment is administered. Nevertheless, recurrences after surgery are quite common (46%) and this evidence deserves further investigations and deeper analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
4
28
1
4
Order By: Relevance
“…Regarding the prognosis, no significant impact was observed in the DD group as compared to the non-DD group. However, as for the prognostic impact of pathologic CR, previous studies, larger in scale than our present study, have shown the existence of a correlation between a higher pathological CR rate and favorable prognosis in patients who underwent induction CRT followed by surgery (20,21). In fact, only one patient relapsed within 2 years in the DD group.…”
Section: Discussioncontrasting
confidence: 56%
“…Regarding the prognosis, no significant impact was observed in the DD group as compared to the non-DD group. However, as for the prognostic impact of pathologic CR, previous studies, larger in scale than our present study, have shown the existence of a correlation between a higher pathological CR rate and favorable prognosis in patients who underwent induction CRT followed by surgery (20,21). In fact, only one patient relapsed within 2 years in the DD group.…”
Section: Discussioncontrasting
confidence: 56%
“…Der Vergleich war aber nicht statistisch signifikant (p = 0,074). Eine adjuvante Therapie wurde in 7 ( im Rahmen prospektiv-randomisierter Studien nicht valide belegt werden [10,11]. Die internationale Multicenter-Phase-II-Studie (CISTAXOL) konnte mit dem multimodalen Therapiekonzept im Stadium IIIA/B erstmals ein 10-Jahres-Langzeitüberleben von 26 % erreichen [12].…”
Section: Statistikunclassified
“…Somit wurde infolge der trimodalen Therapie ein hoher Anteil an "Respondern" (30/46, 65 %) erreicht. Die Remissionsinzidenz ist sehr heterogen verteilt und wird von der Aggressivität der Induktionstherapie beeinflusst [10,29]. Allerdings sind mit steigender Intensität der Induktionstherapie die Toxizitätszunahme und folglich komplikationsbedingte Therapieunterbrechungen zu verzeichnen [17,22].…”
Section: Statistikunclassified
See 1 more Smart Citation
“…Although several case reports have been published, the overall incidence and odds ratio of advanced NSCLC patients reaching a CR has not been systematically defined [42][43][44] . In addition, obtaining a CR could positively reduce the risk of local relapse and distant metastasis for locally advanced NSCLC patients 45,46 , and CR is a potential surrogate marker for survival. As a result, it is of particular importance to determine whether the use of anti-EGFR agents would increase the CR in advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%